Review on identification, underlying mechanisms and evaluation of freezing damage - Dalvi-Isfahan, Mohsen; Jha, Piyush Kumar; Tavakoli, Javad; Daraei-Garmakhany, Amir; Xanthakis, Epameinondas; LeBail, Alain (My University, 2019)
Although freezing is known as the best method of food preservation, physical and chemical changes that occur to the cellular structure during processing and storage may damage the quality of food products. Most freeze damages are associated with ice crystal morphology (size, number, shape and distribution) which in turn affects the microstructure of the frozen food. Therefore, the evaluation of frozen food microstructure provides opportunities for monitoring the ice crystal morphology and also identifies freeze damage at cellular level which can be linked with the final quality of frozen food products. In this review, the most important physical damages that occur during freezing and storage of food matrices are described. In addition, methods for evaluating and observing the morphology of ice crystals and microstructure of frozen food stuffs are comprehensively discussed. An understanding of the freeze damage and their relationship with ice crystal morphology can contribute to the improvement of the freezing process as well as to the frozen product quality.
Keywords: Freeze damage; Microscopy; Cryoconcentration; Mechanical damage; Freeze burn; Recrystallization